Prevention of congenital syphilis in a municipality of the state of Rio Grande do Norte - Rosineide Santana de Brito; Adriana Karla de Oliveira Ferreira (Rev Rene)
The purpose of this exploratory descriptive study was to identify the preventive actions for congenital syphilis in prenatal services of the São Gonçalo do Amarante-RN municipality. Data were collected by means of questionnaires that doctors and nurses filled out at the health unit. The sample was comprised of 81% of the professionals that work in this area. It was concluded that the conduct of each professional is distinct. Some adhere to the prevention guidelines of the Healthy Ministry while others do not, therefore contributing to the prevalence of congenital syphilis in the municipality.